Case-studies in economic development - Okun, Bernard; Richardson, R. W. (New York : Holt, Rinehart and Winston Inc, 1961)
This is a book of readings in the subject of economic development. It should be made clear at the outset that by economic development we refer not only to the problems of "underdeveloped countries", now struggling to extricate themselves from the toils of extreme poverty, but to the growth problems of the "advanced countries" as well.
Includes bibliographical references
osa 16/4/19
Loans
Keywords: Structural adjustment (Economic policy); Africa